IMPLEMENTASI PEMIDANAAN TERHADAP KORPORASI DALAM TINDAK PIDANA KORUPSI DI INDONESIA - Melia Wulandari; Hayatul Ismi; Davit Rahmadan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Indonesia as a country that adheres to the Continental European legal system, which is a legal system inherited from the Netherlands, has also implemented corporal punishment. However, even though Indonesia has embraced corporal punishment, until now there are still few corporations that are made as suspects or defendants in the process of law enforcement against corporations, especially in criminal acts of corruption.The purpose of this thesis, namely: first, To Know the Implementation of Corruption Against Corporations in Corruption in Indonesia. Second, To Know the Obstacles in the Implementation of Penalties Against Corporations in Corruption in Indonesia. This type of research is classified into a type of normative research. With the technique of collecting legal material sources in research carried out by identifying and inventorying primary legal materials, and collecting secondary, tertiary materials obtained through literature, which also ruled the cases sampled.From the results of the study, the reluctance of law enforcers to indict defendants as individuals and not corporations in criminal acts of corruption; because the punishment that the court will bring against the corporation may not be a death penalty or a prison sentence, even though this criminal sanction with sharp sanctions is expected to have a deterrent effect on the perpetrators and satisfy the sense of justice of the people who want the perpetrators to be imprisoned. Second, in proving to prove the "mistake" of the corporation in terms of the element of "against the law", law enforcers find it difficult to obtain theories or doctrines and legal basis regarding "mistakes" of corporations which have turned out to be conflicting among criminal law experts. It is different from theories or doctrines and the legal basis of the "mistakes" of individuals who in general criminal experts agree that only people can have the element of "error". The error of law enforcers proves that acts as an individual error in corporate criminal acts will result in the defendant in some of the above cases being broken free (vrijspraak) by the courtKeywords: Corruption - Corporations – Corruption